Catalytic Hydrophosphination of Allenes Using an Iron(II) β-Diketiminate Complex - Woof, Callum R.; Linford-Wood, Thomas G.; Mahon, Mary F.; Webster, Ruth L. (Synthesis, 2022)
A rare study into the catalytic hydrophosphination of allenes is reported. Employing an Fe(II) β-diketiminate pre-catalyst, the reaction of HPPh2 proceeds with a range of aryl- and alkylallenes. For arylallenes the E-vinyl product forms as the major species, while the 1,1-disubstituted alkene is formed in a larger ratio than the Z-vinyl product (e.g., 6:3:1 as E/1,1/Z). The use of H2PPh results in good yields of the 1,1-disubstituted alkene, where the resultant secondary phosphine product does not undergo further reaction. We postulate a catalytic cycle based on spectroscopic data. Employing an [Fe(salen)]2-µ-oxo pre-catalyst leads to phosphine dehydrocoupling rather than hydrophosphination.
Keywords: iron; homogeneous catalysis; hydrophosphination; allenes; phosphines